Effect of Management System, Parity Orders and Stages of Lactation on Chemical Composition of Camel Milk - Elhassan, Sarra M. B. Mohamed; Dowelmadina, Ibrahim M. M.; El Zubeir, Ibtisam, E. M. (Journal of Veterinary Medicine and Animal Production, 2021)
The present study selected the intensive system in Khartoum North (Khartoum State), traditional nomadic system in both Tamboul (Gezira State) and Moya Mountain (Sennar State) for collection of camel milk samples (25, 23 and 21, respectively) during the period from June to July 2013. The study aimed to evaluate the impact of different management systems, parity orders and stages of lactation on the chemical composition of camel milk from different breeds. The samples were examined to determine the percent of fat, solids not fat, total solids, protein, lactose and density of camel milk. The results indicated that both management systems and stages of lactation had impacted significantly (P≤0.05) the chemical composition of camel milk. Parity order on the other hand did not affected fat, total solids and density of camel milk. Meanwhile the fat, solids not fat, total solids, protein, lactose and density of camel milk decreased with advancement of lactation, i.e from early to late stage of lactation. Milk samples of 4th + 5th parity camels showed the highest fat, solids not fat, total solids, protein, lactose and density compared to other studied parity orders. It was concluded that the chemical composition of camel milk of different breed vary among different management systems and that she-camels grazing in nomadic system utilizing the in rich pasture gave milk with higher compositional content.